Podstawowe problemy rozwoju innowacyjności małych i średnich przedsiębiorstw w Polsce na przełomie XX i XXI stulecia - Czaja, Stanisław; Becla, Agnieszka (Basic Problems of the Developing of the Innovation in Small and Medium Enterprises in Poland at the Turn of the XX and XXI Centuries, 2007)
The article presents some problems of developing small and medium enterprises sector in the Polish economy. Especially, the authors discuss problems of innovatory small and medium enterprises in the comparison to other EU countries, with the use of the Summary Innovation Index.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 79-91